Navigating Resistance And Adaptation: Reinforcing Teachers’ Growth Mindset In Deep Learning Practices Under The Merdeka Curriculum Framework - Yusaini Yusaini (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This study aims to analyze teachers’ resistance toward the implementation of the deep learning approach within the Merdeka Curriculum and to examine the role of growth mindset in reducing such resistance in order to support the achievement of national education goals. The study employed a qualitative descriptive approach supported by quantitative data obtained through a closed-ended questionnaire distributed to teachers across several regions in Indonesia via Google Forms. The instrument consisted of ten questionnaire items representing the variables of resistance to deep learning and growth mindset. Data were analyzed using simple descriptive statistics. The findings indicate that teachers’ resistance should not merely be interpreted as a form of rejection, but rather as a rational response to various challenges, including limited pedagogical competence, insufficient professional training, heavy administrative workloads, and inadequate educational facilities and infrastructure. In addition, some teachers perceived that the deep learning approach had not yet demonstrated significant differences compared to previous instructional approaches, particularly in improving academic achievement and fostering students’ character development. This condition reflects a gap between policy expectations and classroom realities, suggesting that the implementation process remains in a transitional phase. Nevertheless, growth mindset plays a significant role in reducing teachers’ resistance, as educators with a growth-oriented mindset tend to be more open to change, adaptive, and reflective in improving the quality of learning practices. Therefore, the successful implementation of deep learning largely depends on teachers’ readiness, systemic support, and the transformation of educators’ mindsets through comprehensive efforts, such as simplifying administrative demands, improving the quality of professional development programs, and strengthening the learning ecosystem to ensure that educational practices can be implemented effectively and sustainably